Thermally evaporated vanadium-based phthalocyanine for low moisture detection in humidity sensors - Natashah, Fadlan Arif; Lin, Chong Jeng; Hishamuddin, Syaza Nafisah; Coffey, Aidan H.; Zhu, Chenhui; Bawazeer, Tahani M.; Alsoufi, Mohammad S.; Roslan, Nur Adilah; Supangat, Azzuliani (Elsevier, 2024)
Aluminium / vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22-tetrakis(dimethylamino)− 29 H,31 H-phthalocyanine (VTP) / Aluminium, (Al/VTP/Al) has been successfully studied for capacitive humidity sensing. The metal-containing vanadium central atom in the metal phthalocyanine has contributed towards excellent capacitance response at low humidity conditions as low as 10RH. In addition, high surface roughness revealed by atomic force microscopy (AFM) images has also given insight into the low hysteresis lag. The film's large surface area helped prevent the water molecules from accumulating in the VTP pores and capillaries. Grazing-incidence wide and small-angle X-ray scattering (GIWAXS-GISAXS) indicates some face-on crystallite orientation produced by the partially ordered film, impacting the transient performance of the sensor. © 2024 Elsevier Ltd